Exploration of Holistic Character Values on Integrative Thematic Books - Saroh Kurnia; Ganjar Muhammad Ganeswara; Edi Suresman (Indonesian Journal of Primary Education, 2021)
This research is based on the problems related to content materialthat does not emphasize of character education. This research aims to explore the values of the holistic character contained in the integrated thematic book of fourth grade for elementary school and implication in the learning process or student life. This research used qualitative approach with the content analysis objects were several themes in Integrative Thematic learning for fourth grade. And the methods of research used in this research was descriptive. Data collection techniques using documentation and literature study. Based on the exploration results the, character values contained in the integrative thematic book were: [1] The values of holistic character in the textbook are Love of God and all of His Creations, Responsibility, Tolerance, Mutual Cooperation, and Perseverance; Although lacks in the aspects of language, text function, incomplete discourse and the frequency of uneven character values loads, but with the holistic character, can balance cognitive, affective and psychomotor loads in integrative thematic books [2] The implication for learning or student life is that it has not made abstract characters more concrete because holistic characters are more contained in narrative texts compared to practice during learning and in daily life and the use of forms of linguistic exposure must use language that is often found in elementary school children. The results of this study provide several recommendations for further studies, programs, teachers, and researchers that can be taken into consideration integration character education and improving the contents in integrative thematic books.